Perceptions and recommendations by scientists for a potential release of genetically modified mosquitoes in Nigeria (2014)
Background: The use of genetically modified mosquitoes (GMMs) for the control of malaria and other mosquito-borne diseases has been proposed in malaria-endemic countries, such as Nigeria, which has the largest burden in Africa.Scientists are major stakeholders whose opinions and perceptions can adversely affect the success of the trials of GMMs if they are not involved early. Unfortunately, information on the awareness of Nigerians scientists and their overall perception of the GMMs is practically non-existent in the literature. Therefore, this study aimed at understanding how receptive Nigerian scientists are to a potential release of GMMs for the control of malaria. Methods: The sample consisted of 164 scientists selected from academic and research institutions in Nigeria. Data were collected from participants using a semi-structured, self-administered questionnaire. Questions were asked about the cause and prevention of malaria, genetic modification and biotechnology. Specific questions on perception and acceptable conditions for the potential release of GM mosquitoes in Nigeria were also covered. Results: All participants cited mosquitoes as one of several causes of malaria and used various methods for household control of mosquitoes. The main concerns expressed by the scientists were that GMMs can spread in an uncontrolled way beyond their release sites (89%) and will mate with other mosquito species to produce hybrids with unknown consequences (94.5%). Most participants (92.7%) agreed that it was important that before approving the release of GMMs in Nigeria, there had to be evidence of contingency measures available to remove the GMMs should a hazard become evident during the course of the release. In general, a majority (83.5%) of scientists who participated in this study were sceptical about a potential release in Nigeria, while 16.5% of the participants were in support. Conclusions: Although a majority of the participants are sceptical about GMMs generally, most encourage the use of genetic modification techniques to make mosquitoes incapable of spreading diseases provided that there are contingency measures to remove GMMs if a hazard becomes evident during the course of the release.